Enhancement of Teaching Learning Process by Blended Teaching - Janapati, Ravichander; Girirajan, B.; Leo Joseph, L. M. I.; Bikshalu, K. (Journal of Engineering Education Transformations, 2022)
The teaching-learning process is one of the most fun ways to learn for a lifetime of a learning experience and inner competence. Teaching provides a kind of opportunity to share free trade of information and ideas in a useful environment. Effective teaching should follow the strategic path of dealing with the main motto of student vision and innovation. Drawing on the concentration of students in the classroom is a great influence, which gives the image of a good class. The experiential-based learning approach relates the concept of teaching to industrial standards and applications, where the student gets to know why, where, and what to learn. Current and future generations of students are born in the technological age and are more passionate about utilizing web resources. The traditional blackboard teaching class seems passive and, in experiential that fails to grab the attention of millennials. Blended teaching (Flipped Classroom) can make the classroom dynamic and interactive. We have practiced some active learning techniques such as Flipped STAD, reciprocal teaching, and flipped classroom to make the classroom interactive and dynamic. This article discusses the experiences and barriers of blended teaching combined with classroom practices. This article will help the aspirants who are in thirst to adopt innovation in teaching.